A double blind, randomized, placebo controlled, phase IV, proof-of-concept, comparative study to evaluate the efficacy and safety of Swasawin asthaloc tablets when given as add-on therapy in patients suffering from mild to moderate persistent bronchial asthma - Karande, Shilpa P.; Munshi, Renuka P.; Kumbhar, Dipti A. (International Journal of Research in Medical Sciences, 2017)
Background: Asthma, known as “Tamaka Shwasa” in Ayurveda, as a chronic inflammatory disorder of the airways associated with increased airway hyper-responsiveness, recurrent episodes of wheezing, breathlessness, chest tightness and coughing, particularly at night/early morning. The key component to improving control and preventing attacks is the avoidance of triggers. Swasawin Asthaloc tablet, a polyherbal proprietary medication, is claimed to be effective in asthma. The Objective of the study was to evaluate the safety and efficacy of Swasawin Asthaloc tablets when given as add-on therapy to patients suffering from mild to moderate persistent bronchial asthma. Methods: The study was initiated after receiving Institutional Ethics Committee approval. Patients suffering from mild-to-moderate persistent bronchial asthma were randomized to 2 study groups after written informed consent process for 6 months. Group I received the study medication Swasawin Asthaloc tablet (1 tablet twice daily) in addition to regular anti-asthmatic medications (inhaler ± oral medications). Group II received Placebo tablets in a similar dose as add-on therapy. The study efficacy parameters included spirometry, breath holding time (BHT), Asthma symptom score and Ayurvedic Asthma symptom score. Results: 60 patients were enrolled in the study, of which 50 patients completed the study. In case of spirometry, both FEV1 and PEFR values showed statistically significant improvement at the end of 6 months therapy. Significant improvement in the Breath Holding Time (BHT), Ayurvedic Asthma symptom score and Asthma symptom score was observed in the active group as compared to the baseline (p <0.001). Conclusions: Add-on therapy with Swasawin Asthaloc tablets helped in reducing bronchial inflammation and improving asthmatic symptoms by virtue of its anti-inflammatory, bronchodilatory and antihistaminic properties. Hence it can be used as add-on therapy in patients with mild-to-moderate persistent bronchial asthma and may decrease the need for rescue medications especially steroids.